2010
DOI: 10.1016/j.bpj.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan as a Molecular Shovel in the Glycosyl Transfer Activity of Trypanosoma cruzi Trans-sialidase

Abstract: Molecular dynamics investigations into active site plasticity of Trypanosoma cruzi trans-sialidase, a protein implicated in Chagas disease, suggest that movement of the Trp(312) loop plays an important role in the enzyme's sialic acid transfer mechanism. The observed Trp(312) flexibility equates to a molecular shovel action, which leads to the expulsion of the donor aglycone leaving group from the catalytic site. These computational simulations provide detailed structural insights into sialyl transfer by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Molecular dynamics (MD) simulations have shown that two hydrophobic residues, Tyr-119 and Trp-312, play important roles in TcTS flexibility by controlling the entry of substrates into the catalytic pocket (17,18). Classical (19) and hybrid quantum mechanics/MD (20) simulations combined with mutagenesis studies (19,21) have identified other key residues that probably contribute to the plasticity of the binding site.…”
mentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have shown that two hydrophobic residues, Tyr-119 and Trp-312, play important roles in TcTS flexibility by controlling the entry of substrates into the catalytic pocket (17,18). Classical (19) and hybrid quantum mechanics/MD (20) simulations combined with mutagenesis studies (19,21) have identified other key residues that probably contribute to the plasticity of the binding site.…”
mentioning
confidence: 99%
“…Recently, Mitchell et al . found that Trp312 in TcTS acts as a shovel when the lactose moiety moves from or into the active site . Something similar could happen in TrSA.…”
Section: Methodsmentioning
confidence: 77%
“…For instance, from molecular dynamics simulations it is known that the key hydrophobic residues Y119 and W312 confer flexibility to the catalytic cleft mouth and allow substrates to access the catalytic pocket in a controlled manner (Demir and Roitberg, 2009; Mitchell et al, 2010). Other key residues, which possibly contribute to the plasticity of binding site, were identified by mutagenesis studies (Paris et al, 2001; Carvalho et al, 2010b) or by hybrid quantum mechanics/molecular mechanics simulations (Pierdominici-Sottile and Roitberg, 2011).…”
Section: Tcts Mechanismmentioning
confidence: 99%
“…Despite great advances made toward TcTS inhibition, works highlighting the enzyme’s plasticity (Demir and Roitberg, 2009; Mitchell et al, 2010) showing the existence of an acceptor binding site (Todeschini et al, 2004; Damager et al, 2008) suggest that the structure of TcTS with two cavities would be a better framework for rational drug design aimed to TcTS inhibition.…”
Section: Inhibition Of Sialic Acid Transference By Tctsmentioning
confidence: 99%